Comparative evaluation of microbial colony counts of sutures with and without use of periodontal pack after modified Widman flap surgery - Ahmad Moghareh Abed; Jaber Yaghini; Narges Mazaheri Tehrani (Isfahan University of Medical Sciences, 2011)
Introduction: In most cases after periodontal surgery, the surgical area is covered with surgical packs. Recent studies suggest that use of periodontal packs after periodontal flap surgery is not necessary and some patients may be irritated by them. The aim of this study was to determine microbiological contamination of a periodontal pack (Coe-pak) by determining microbial colony counts of surgical sutures after modified Widman flap surgery.Materials and Methods: In this clinical trial, thirty-two patients needing periodontal surgeries at least in two quadrants of jaws were selected. In one quadrant, after surgery the surgical area was covered with periodontal pack randomly and the other quadrant was left without any dressing. After a week the sutures were removed and microbiological colony counts were determined. Finally microbial colony counts in the two groups were compared between the two groups by paired sample test using SPSS software (α=0.05). Results: The mean colony counts with and without periodontal pack were 10187±2900 and 9812±3042, respectively, with no statistically significant differences between the two groups (p value = 0.602).Conclusion: The results of this research showed that sutures have microbial contamination with or without use of periodontal packs and these materials have no effect on microbial contamination. Key words: Microbial colon, Modified Widman flap surgery, Periodontal pack (Coe-pak).